Pilot cadaveric study on the feasibility of cricothyroidotomy and the associated complications in 30 cats - Delle Cave, Julia A.; Larcheveque, Samuel R.; Martin, Edouard; O’Toole, Elizabeth (Frontiers in Veterinary Science, 2024)
Objectives The study’s primary goal was to assess the feasibility of the cricothyroidotomy technique (CTT) in cats and evaluate its success rate (i.e., secure airway access). Secondary outcomes were the assessment of the subjective difficulty of airway access based on body score condition and weight. Further secondary outcomes consisted of procedural time and scoring of associated complications. The current study hypothesized that the CTT procedure would provide secure airway access with a reasonable success rate. Materials and methods A prospective experimental study assessing the performance of CTT and associated complications was conducted on 30 feline cadavers. A procedural datasheet was completed to subjectively grade difficulty of landmark palpation, guide placement and tube placement and expected success of the procedure. A dissection was then performed post-procedure by a blinded observer to evaluate for any associated damages. Results CTT was successful in securing an airway in 100% of the cats. The time to completion of the CTT was rapid, with a median time of 49 s (ranging from 31 to 90 s) for securing an airway. Of importance, this procedure was judged to be overall easy (median “ease of procedure score” of 7/10; ranging from 3 to 10) by the experimenters. The post-procedural lesion rate was elevated (76.7%) in this population of cats, though based on the lesion scores, was deemed mild in 73.9% of the cases. Clinical significance CTT warrants consideration as the primary option for emergency front-of-neck airway access for cats although further studies are necessary.